Shāfi'ī Literature in Indonesia: A Historical Account - Suud Sarim Karimullah (Islamica: Jurnal Studi Keislaman, 2022)
Al-Shāfi‘ī is one of the moderate Islamic scholars and is seen as the most crucial party in the history of the civilization of Islamic legal thought. This study reveals the various fiqh literature of the Shāfi‘ī madhhab, which are spread in the Muslim world and their development in Indonesia by tracing historically through prioritizing an understanding of historical facts using heuristic methods through critical analysis sourced from library data. Then, this study states that the role of the Shāfi‘ī students and scholars in the dissemination of Shāfi‘ī literature greatly influences the existence of the Shāfi‘ī madhhab in the life of the Islamic world, including Indonesia. The dynamics of Indonesian legal opinion initiated by several figures from the Shāfi‘ī madhhab have made the madhhab continue to exist and be used as a reference in determining Islamic law in Indonesia. Moreover, various Shāfi‘ī madhhab of literature written by Indonesian scholars has been discovered. Thus, the Shāfi‘ī madhhab is always relevant to be used as a guide for Islamic law in Indonesia.